Pengurangan Nyeri Dismenore Primer pada Remaja Putri dengan Kompres Hangat - Retno Hayu Pangesti; Gangsar Indah Lestari; Riyanto Riyanto (Jurnal Kesehatan Metro Sai Wawai, 2017)
Background: The incidence of dysmenorrhea in the world is very high. On average more than 50% of women in each country experience dysmenorrhea. Purpose:: This study aims to determine the effect of warm compresses on reducing primary dysmenorrhea pain in adolescent girls at SMA Negeri 4 Metro City in 2017. Methods: This research study is a one group pretest posttest design experiment conducted in April 2017. Warm compresses as a variable intervention and pain dysmenorrhea as effect variables. The study population was all young women who experienced primary dysmenorrhea with a sample of 23 people taken by consecutive sampling technique. Data collection by observation. Bivariate analysis using non parametric dependent statistical tests with Wilcoxon test. Results: The results showed the average of primary dysmenorrhea pain before a warm compress with a scale of 7.48, after a warm compress with a scale of 4.74 and there is an effect of a warm compress on the reduction of primary dysmenorrhea pain. Conclusions: The study conclusions there is a reduction in primary dysmenorrhea with warm compresses. The need for young women to use warm compresses as a way to treat primary dysmenorrhea early.